Hedging effectiveness in EU energy market: A case study - Petrou, Andreas; Eriotis, Nikolaos; Poutos, Evangelos; Boufounou, Paraskevi (Energy Economics Letters, 2024)
The current conditions in the European Union energy market are closely linked to significant fluctuations in both demand (due to the marked reduction in economic activity across the EU region due to the implementation of protection measures against COVID-19) and supply (characterized by high volatility in electricity pricing due to irregular fluctuations in fossil fuel prices). Given these challenging conditions, energy companies are forced to adopt hedging strategies to navigate the complexities associated with the extensive market risks. This study empirically examines the impact of the implementation of hedging strategies (measured by the value of financial derivatives relative to the total assets of company values) on financial value (assessed using the Tobin Q ratio) of power generation companies operating in the EU region for 2016 - 2021. The results, derived from an econometric study using panel data analysis, revealed that a potential increase in the value of financial derivatives as a percentage of total assets held by power generation firms in the EU region positively affects the Tobin Q index and, consequently, enhance their financial value. There is no statistically significant evidence to support the relationship between the growth of the domestic forward electricity market and the Tobin's Q index.